1995
DOI: 10.1006/viro.1995.1379
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of the Epstein-Barr Virus ZEBRA Protein's Capacity to Disrupt Latency by the Addition of Heterologous Activation Regions

Abstract: The ZEBRA protein has a unique biological function among herpesviral proteins. It is responsible for the disruption of Epstein-Barr virus (EBV) latency and the induction of the lytic cycle. ZEBRA is a bZIP transcriptional activator which binds as a dimer to 7-bp response elements within EBV promoters and is directly involved in the stimulation of virus replication at the EBV lytic origin. We have employed the ZEBRA/EBV biological system to test whether a heterologous activation domain can substitute for anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
8
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…In these studies we address the domain requirements of ZEBRA in human B lymphocytes latently infected with EBV. Previous work from this laboratory has shown that ZEBRA's activation domain can be replaced by potent acidic activation regions (5). Here those studies are extended to nonacidic activation domains.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…In these studies we address the domain requirements of ZEBRA in human B lymphocytes latently infected with EBV. Previous work from this laboratory has shown that ZEBRA's activation domain can be replaced by potent acidic activation regions (5). Here those studies are extended to nonacidic activation domains.…”
mentioning
confidence: 86%
“…B-cell lines were transfected by using a Bio-Rad Gene Pulser apparatus with a capacitance extender, at 960 F and 0.25 kV in 0.4 ml of complete medium. After electroporation, cells were maintained in RPMI medium with 8% fetal calf serum for 2 to 4 days at 37°C under a 5% CO 2 atmosphere (5).…”
mentioning
confidence: 99%
See 3 more Smart Citations